3 eggs minus 4 eggs is. . . well,
an egg in the hole! (or -1 egg)
=)
2007-04-08 07:56:38
·
answer #1
·
answered by mikedotcom 5
·
0⤊
0⤋
In case it is (3x) ^2 - (4x) ^2 then the answer is - 7x^2
In case it is 3 (x ^2) - 4 (x^2) then the answer is - x^2
2007-04-08 08:01:34
·
answer #2
·
answered by Anonymous
·
0⤊
0⤋
3x^2 + 4x - 7 - (x^2 - 2x + 6 ) = 2x^2 + 6x - 13
2016-05-20 00:53:59
·
answer #3
·
answered by ? 3
·
0⤊
0⤋
3x^2 - 4x^2 = (3-4)x^2 = (-1)x^2 = -x^2
Just remember that you can work on the coefficients but the variables, whatever their power, are sacrosanct
2007-04-08 07:56:24
·
answer #4
·
answered by kellenraid 6
·
0⤊
1⤋
3x^2-4x^2= -x ^2 =-1(x^2)
2007-04-08 09:27:15
·
answer #5
·
answered by Dave aka Spider Monkey 7
·
0⤊
0⤋
3x3 = 9 - 4x4 = 16
9-16 = -7
if you multiplied that supposing that both are ambigalent, the first one satisfies the second one so the answer would be :
4x
2007-04-08 07:57:19
·
answer #6
·
answered by Anonymous
·
0⤊
0⤋
The answer would be -x squared.
They both are like terms, so you can just subtract the number portion of them to get the answer.
Hope this helps : )
2007-04-08 07:57:01
·
answer #7
·
answered by anicoleslaw 5
·
0⤊
0⤋
3 of anything - 4 of anything = -1 of that thing
so second answer
2007-04-08 07:57:23
·
answer #8
·
answered by hustolemyname 6
·
0⤊
0⤋
-x squared.
2007-04-08 07:56:21
·
answer #9
·
answered by Anonymous
·
0⤊
0⤋
3x² - 4x² =
- x²
- - - - - - - - s-
2007-04-08 09:13:07
·
answer #10
·
answered by SAMUEL D 7
·
0⤊
0⤋